Innate Immune Training with Bacterial Extracts Enhances Lung Macrophage Recruitment to Protect from Betacoronavirus Infection - Manuel Salzmann (Karger Publishers, 2021)
Training of the innate immune system with orally ingested bacterial extracts was demonstrated to have beneficial effects on infection clearance and disease outcome. The aim of our study was to identify cellular and molecular processes responsible for these immunological benefits. We used a murine coronavirus (MCoV) A59 mouse model treated with the immune activating bacterial extract Broncho-Vaxom (BV) OM-85. Tissue samples were analysed with qPCR, RNA sequencing, histology, and flow cytometry. After BV OM-85 treatment, interstitial macrophages accumulated in lung tissue leading to a faster response of type I interferon (IFN) signalling after MCoV infection resulting in overall lung tissue protection. Moreover, RNA sequencing showed that lung tissue from mice receiving BV OM-85 resembled an intermediate stage between healthy and viral infected lung tissue at day 4, indicating a faster return to normal tissue homoeostasis. The pharmacologic effect was mimicked by adoptively transferring naive lung macrophages into lungs from recipient mice before virus infection. The beneficial effect of BV OM-85 was abolished when inhibiting initial type I IFN signalling. Overall, our data suggest that BV OM-85 enhances lung macrophages allowing for a faster IFN response towards a viral challenge as part of the oral-induced innate immune system training.